An in vitro investigation of the effects of excitatory amino acids and serotonin on mesencephalic trigeminal neurons. - Pelkey, Kenneth Allen. (University of Ottawa (Canada), 1997)
In the present investigation we have performed intracellular recordings from mesencephalic trigeminal nucleus (MeV) neurons in an in vitro brain slice preparation to reevaluate the effects of two likely candidate neurotransmitters, glutamate and serotonin, on MeV neurons. Recorded neurons were observed to depolarize in response to exogenously applied glutamate, N-methyl-D-aspartic acid (NMDA), kainate (KA), and (R,S)-$\alpha$-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA). The agonists generally evoked larger responses than glutamate, and exhibited a long duration desensitization requiring approximately ten minutes for full recovery. Some cross-desensitization between the glutamate agonists was also observed. MeV neurons exhibit voltage-dependent subthreshold high-frequency oscillatory activity that may be activated during excitatory amino acid (EAA)-induced depolarizations to enhance their excitability. Exogenously applied serotonin was observed to cause small depolarization of MeV neurons accompanied by substantial reductions in input resistance. The response was determined to result from activation of the inward rectifier, I$\rm\sb{h}.$ Applications of forskolin, 8-bromo-cAMP, and IBMX, substances known to elevate intracellular adenosine $3\sp\prime,5\sp\prime$-cyclic monophosphate (cAMP), were observed to mimic the serotonin response suggesting that the second messenger system mediating the serotonin response involves activation of adenylyl cyclase leading to an increase in intracellular cAMP. The serotonin response could be reproduced with the serotonin agonist, 5-carboxamidotryptamine (5-CT), but not by 8-hydroxy-2-(di-N-propylamino)-tetralin (8-OH-DPAT), and could be antagonized by ketanserin but not by methiothepin. It is speculated that serotonin input contributes to the excitability level of MeV neurons by regulating the degree of activation of I$\rm\sb{h}.$ (Abstract shortened by UMI.)
Keywords: Biology, Neuroscience.